Adjuvant Chemotherapy Does Not Improve Recurrence-Free Survival in Patients With Stage 2 or Stage 3 Rectal Cancer After Neoadjuvant Chemoradiotherapy and Total Mesorectal Excision. Issue 4 (April 2020) - Voss, Rachel K.; Lin, Jane C.; Roper, Michelle T.; Al-Temimi, Mohammed H.; Ruan, Joseph H.; Tseng, Warren H.; Tam, Michael; Sherman, Matthew J.; Klaristenfeld, Daniel D.; Tomassi, Marco J.
Abstract : BACKGROUND: Current guidelines for locally advanced stage 2/3 rectal cancer recommend neoadjuvant chemoradiotherapy followed by total mesorectal excision and adjuvant chemotherapy. The oncologic benefit of adjuvant chemotherapy has not been consistently demonstrated. OBJECTIVE: The purpose of this study was to evaluate disease recurrence and survival in patients with rectal cancer who received adjuvant chemotherapy after chemoradiotherapy and total mesorectal excision. DESIGN: This was a retrospective review of patients with stage 2/3 rectal cancer after chemoradiotherapy and surgery, based on receipt of adjuvant chemotherapy. SETTINGS: The study was conducted at the Kaiser Permanente Southern California system of 14 hospitals and associated clinics. PATIENTS: A total of 862 patients with stage 2/3 rectal cancer diagnosed and treated between January 1, 2005, and December 31, 2016, were included in this study. INTERVENTIONS: The study involved neoadjuvant chemoradiotherapy followed by total mesorectal excision with or without adjuvant chemotherapy. MAIN OUTCOME MEASURES: The primary end point was recurrence-free survival. RESULTS: A total of 348 stage 2 and 514 stage 3 patients were included; 660 patients (76.6%) underwent adjuvant chemotherapy. Mean patient follow-up after surgery was 63.0 months (range, 3–160). Multivariable analysis showed that yp stage (HR for yp stage 2 = 4.74; yp stage 3 = 8.83) and en bloc resection (HR = 1.76) were the only variables that significantly predicted disease recurrence. Neither pretreatment tumor stage nor receipt of adjuvant chemotherapy was significantly associated with recurrence-free survival. Log-rank testing failed to demonstrate significant recurrence-free survival improvement after receipt of adjuvant chemotherapy in any patient subgroup. LIMITATIONS: The study was limited by selection bias attributed to the nature of a retrospective study without patient randomization or predefined treatment protocol. CONCLUSIONS: In stage 2/3 rectal cancer treated with chemoradiotherapy and surgery, the addition of adjuvant chemotherapy was not associated with decreased recurrence-free survival in the entire cohort or in any subgroup, whereas tumor response to chemoradiotherapy is closely associated with disease recurrence. These findings have important consequences for treatment and surveillance decisions for patients with rectal cancer. Presurgical efforts that maximize tumor downstaging, such as total neoadjuvant therapy, may produce better oncologic outcomes than traditional adjuvant chemotherapy. See Video Abstract at http://links.lww.com/DCR/B134 . LA QUIMIOTERAPIA ADYUVANTE NO MEJORA LA SOBREVIDA LIBRE DE RECURRENCIA EN PACIENTES CON CÁNCER DE RECTO ESTADÍOS II O III DESPUÉS DE RADIO-QUIMIOTERAPIA NEOADYUVANTE Y ESCISIÓN TOTAL DEL MESORRECTO: ANTECEDENTES: Las guías actuales para el tratamiento de cáncer rectal en estadio II-III localmente avanzado, recomiendan la radio-quimioterapia neoadyuvante con escisión total del mesorrecto seguidas de quimioterapia adyuvante. El beneficio oncológico de la quimioterapia adyuvante no ha sido demostrado de manera fehaciente. OBJETIVO: Evaluar la recurrencia y sobrevida a la enfermedad en pacientes con cáncer rectal que recibieron quimioterapia adyuvante después de radio-quimioterapia y escisión total del mesorrecto. DISEÑO: Revisión retrospectiva de pacientes con cáncer rectal en estadios II-III después de radio-quimioterapia y cirugía, basada en la recepción de quimioterapia adyuvante. CONFIGURACIÓN: Sistema Permanente de Kaiser Sur-Californiano de 14 hospitales y clínicas asociadas. PACIENTES: 862 pacientes con cáncer rectal en estadio II-III diagnosticados y tratados entre el 1 de Enero 2005 y el 31 de Diciembre 2016. INTERVENCIONES: Radio-quimioterapia neoadyuvante seguida de escisión total del mesorrecto +/- quimioterapia adyuvante. PRINCIPALES RESULTADOS: El objetivo primario fue la sobrevida libre de recurrencia. RESULTADOS: Fueron incluidos 348 pacientes en estadio II y 514 en estadio III. 660 pacientes (76, 6%) se sometieron a quimioterapia adyuvante. El seguimiento medio de cada paciente después de la cirugía fué de 63.0 meses (rango, 3–160). El análisis multivariable mostró que la etapa yp (Cociente de riesgo para estadío yp II = 4.74 y estadío yp III = 8.83) y la resección en bloque (Cociente de riesgo = 1.76) fueron las únicas variables que predijeron significativamente la recurrencia de la enfermedad. Ni el estadío tumoral previo al tratamiento ni la recepción de quimioterapia adyuvante se asociaron significativamente con la sobrevida libre de recurrencia. Las pruebas de rango logarítmico no pudieron demostrar una mejoría significativa de la sobrevida libre de recurrencia después de recibir quimioterapia adyuvante en cualquier subgrupo de pacientes. LIMITACIONES: Sesgo de selección, debido al estudio retrospectivo sin aleatorización de los pacientes o protocolo de tratamiento predefinido. CONCLUSIONES: En casos de cáncer de recto estadíos II-III tratados con radio-quimioterapia y cirugía, la adición de quimioterapia adyuvante no se asoció con una disminución de la sobrevida libre de recurrencia en toda la cohorte o en ningún subgrupo, mientras que la respuesta tumoral a la radio-quimioterapia está estrechamente asociada con la recurrencia de la enfermedad. Estos hallazgos tienen consecuencias importantes en la decisión del tratamiento y la vigilancia en pacientes con cáncer de recto. Los esfuerzos pre-quirúrgicos que maximizan la reducción del tamaño del tumor, como la terapia neoadyuvante total, pueden producir mejores resultados oncológicos que la quimioterapia adyuvante tradicional. Consulte Video Resumen en http://links.lww.com/DCR/B134 . Abstract : Supplemental Digital Content is available in the text.